SURVEI KINERJA 23 PROGRAM DEDIKASI IDAMAN DI KUTAI KARTANEGARA - Novianto, Efri (Magister Administrasi Publik FISIP Universitas Mulawarman, 2023)
This research is to describe the public's perception of the performance of the Kutai Kartanegara government using a survey method in eleven sub-districts and 280 respondents. Based on the survey results, the performance of the health sector received the highest score of 77.95 while the lowest was in the field of providing employees with a score of 56.07. Overall, the performance of the general government in Kutai Kartanegara Regency received a score of 70.90, which is included in category C or medium. Another finding is that the majority of respondents (57.09%) are not aware of the 23 dedication programs that are strategic projects for the government of Kutai Kartanegara Regency. The program that is most widely known by the public is the 50 Million per RT (Kukar Bebaya) program of 71.10%, while the program that is least known to the public is the area-based agricultural development program which is only known by 22.50%. The performance of Kukar Care for Health Program has the highest score, namely 77.22, while the lowest performance is in the Area-Based Agriculture development Program with a score of 69.44. Overall, the average performance of the 23 dedication programs in Kutai Kartanegara Regency was a score of 73.68, which is in category C or medium.